Slovenski (ljubljanski) šport v primežu globalizacije in tranzicije - Šugman, Rajko (Šport (Ljubljana), 2016)
In the past 20 years, huge or even tectonic shifts have happened in sports on the global scale. The short presentation of the results in this contribution aims to reveal the influence of these shifts at the time of introducing the new, i.e. changed, political system in Slovenia in 1991, especially in the capital city Ljubljana. The question is: were all the changes to the sport system truly necessary when we gained our statehood, or were some areas changed hastily and in an unplanned way to benefit the state so that many burdens of the development of sport were transferred to it. Only the results of a research project can show the real facts, and this contribution is leading the way to such research.
Keywords: globalisation; globalizacija; Ljubljana; sport; šport; transition; tranzicija